Acidification effects on isolation of extracellular vesicles from bovine milk - Rahman, Md. Matiur (PLoS One, 2019)
Bovine milk extracellular vesicles (EVs) attract research interest as carriers of biologically active cargo including miRNA from donor to recipient cells to facilitate intercellular communication. Since toxicity of edible milk seems to be negligible, milk EVs are applicable to use for therapeutics in human medicine. Casein separation is an important step in obtaining pure EVs from milk, and recent studies reported that adding hydrochloric acid (HCl) and acetic acid (AA) to milk accelerates casein aggregation and precipitation to facilitate EV isolation and purification; however, the effects of acidification on EVs remain unclear. In this study, we evaluated the acidification effects on milk-derived EVs with that by standard ultracentrifugation (UC). We separated casein from milk by either UC method or treatment with HCl or AA, followed by evaluation of EVs in milk serum (whey) by transmission electron microcopy (TEM), spectrophotometry, and tunable resistive pulse sensing analysis to determine EVs morphology, protein concentration, and EVs size and concentration, respectively. Moreover, we used anti-CD9, -CD63, -CD81, -MFG-E8, -HSP70, and -Alix antibodies for the detection of EVs surface and internal marker proteins by western blot (WB). Morphological features of EVs were spherical shape and similar structure was observed in isolated EVs by TEM. However, some of the EVs isolated by HCl and AA had shown rough surface. Although protein concentration was higher in whey obtained by UC, EV concentration was significantly higher in whey following acid treatment. Moreover, although all of the targeted EVs-marker-proteins were detected by WB, HCl- or AA-treatments partially degraded CD9 and CD81. These findings indicated that acid treatment successfully separated casein from milk to allow efficient EV isolation and purification but resulted in partial degradation of EV-surface proteins. Our results suggest that following acid treatment, appropriate EV-surface-marker antibodies should be used for accurate assess the obtained EVs for downstream applications. This study describes the acidification effects on EVs isolated from bovine milk for the first time.